IMPLEMENTASI LECTORA INSPIRE SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MINAT BELAJAR BAHASA ARAB SISWA KELAS XI AGAMA DI MAN GODEAN - Auline Oktaria (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2016)
This research is a class action research. The research subjects are all students of class XI majoring in Religion at MAN Godean Yogyakarta on academic year 2012/2013. The number of students is 15 people. The results show that: (1) Learning Arabic with Lectora Inspire media can increase student learning interest of class XI Religion major at MAN Godean. This indicates an increased interest in student learning after the end of the action by using Lectora Inspire media; (2) Arabic learning is carried out in computer labs and in classrooms using LCD and projectors. At the time of learning in the computer laboratory, students can learn independently because Lectora Inspire has provided the material accompanied by instruction and practice questions in it, while the teacher only acts as a facilitator which forms student active learning. The material presented through Lectora Inspire comes with various animations, images, colors and sounds, so it does not make students uninterested. During classroom learning sessions, students form discussion groups. There is a discussion guide on Lectora Inspire displayed through the projector; (3) What makes the students feel interested in learning Arabic language using Lectora Inspire media are: the existence of rewards in the form of praise and applause, motivating teachers, and creating an active and fun learning atmosphere.